2012
DOI: 10.1097/ccm.0b013e318232d97e
|View full text |Cite
|
Sign up to set email alerts
|

Potential long-term benefits of acute hypothermia after spinal cord injury

Abstract: Objective Neuroprotection by hypothermia has been an important research topic over last two decades. In animal models of spinal cord injury (SCI), the primary focus has been assessing effects of hypothermia on behavioral and histological outcomes. While a few studies have investigated electrophysiological changes in descending motor pathways with motor evoked potentials recorded during cooling, we report here, hypothermia induced increased electrical conduction in the ascending spinal cord pathways with somato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 32 publications
0
48
0
Order By: Relevance
“…The core temperature was maintained at 37°C -0.5°C with the help of a heating pad for 1 hour after the time of contusion or laminectomy and prior to inducing hypothermia. After 1 hour, general hypothermia was induced by spraying the rat with alcohol mist (70% ethanol) and using an electric fan until the core temperature dropped to 32°C -0.5°C, as previously described (Shin et al, 2006;Jia et al, 2008;Maybhate et al, 2012). The induction period lasted 25 to 30 minutes.…”
Section: Induction Of General Hypothermiamentioning
confidence: 99%
See 2 more Smart Citations
“…The core temperature was maintained at 37°C -0.5°C with the help of a heating pad for 1 hour after the time of contusion or laminectomy and prior to inducing hypothermia. After 1 hour, general hypothermia was induced by spraying the rat with alcohol mist (70% ethanol) and using an electric fan until the core temperature dropped to 32°C -0.5°C, as previously described (Shin et al, 2006;Jia et al, 2008;Maybhate et al, 2012). The induction period lasted 25 to 30 minutes.…”
Section: Induction Of General Hypothermiamentioning
confidence: 99%
“…We previously showed that 2-hour general hypothermia in rats with moderate contusive SCI leads not only to improved motor behavior and increased somatosensory evoked potential (SSEP) amplitude, but also to increased N1-latency of SSEP, for up to 4 weeks after injury (Maybhate et al, 2012). Because SSEPs are the response at the primary somatosensory cortex to stimulus of the periphery, a key question is how cortical temperature is affected during the period of hypothermia administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 A recent study revealed beneficial effect of hypothermia on somato-sensory and motor-evoked potentials. 6 Our reported experience of 14 cervical SCI patients revealed that systemic hypothermia induced via an intravascular catheter and continued for 48 h showed improved functional outcome and appeared safe compared with a historical control group. 7,8 In this article we describe a larger series of cervical SCI patients based on our extended, single center experience of hypothermia treatment that now spans over 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A recent study revealed beneficial effect of hypothermia on somato-sensory and motor-evoked potentials. 6 Our reported experience of 14 cervical SCI patients revealed that systemic hypothermia induced via an intravascular catheter and continued for 48 h showed improved functional outcome and appeared safe compared with a historical …”
mentioning
confidence: 99%